1997
DOI: 10.1210/jc.82.12.3926
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Glucocorticoid Replacement Therapy on Growth, Bone Mineral Density, and Bone Turnover Markers in Children with Congenital Adrenal Hyperplasia

Abstract: Even with current so called physiologic doses of glucocorticoid replacement therapy, children with congenital adrenal hyperplasia (CAH) often show relative short stature and delayed bone maturation, an observation that suggests possible long-term effects on bone metabolism of daily transient post-absorptive hypercortisolemia. In 28 patients with 21-hydroxylase or 17 alpha-hydroxylase deficiency (16 females and 12 males, ages 4.9-22 yr) who had received oral cortisol 10-15 mg/M2/day for 4.7-22 yr, we studied co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 0 publications
4
68
0
2
Order By: Relevance
“…There was only a tendency for NC patients to have not significantly higher osteocalcin levels, reflecting either a better osteoblast function following a lower corticosteroid dosage or perhaps only a different age. Our results on bone markers of neoformation and resorption are in agreement with those of Girgis and Winter [4], while other authors found lower than normal osteocalcin [22, 23, 24]and NTx [24]levels in their patients. There is no clear explanation for these different findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There was only a tendency for NC patients to have not significantly higher osteocalcin levels, reflecting either a better osteoblast function following a lower corticosteroid dosage or perhaps only a different age. Our results on bone markers of neoformation and resorption are in agreement with those of Girgis and Winter [4], while other authors found lower than normal osteocalcin [22, 23, 24]and NTx [24]levels in their patients. There is no clear explanation for these different findings.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings of a reduced aBMD are consistent with those of one study in adults [8], but not with others carried out in children and young adults [4, 5, 6]. The reason for the divergent results is not clear, however we think that differences in patient selection and/or the fact that our group of patients was larger than that evaluated in other studies might be an explanation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In children and young adults, bone mineral density (BMD) was reported to be increased (4), normal (5,6), or decreased (7). Other pediatric studies found decreased BMD in males (8), in long-term treated girls (9), and at puberty (10).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies are scarce. Common to all reports, however, is short stature and often some degree of obesity [3, 11, 12, 13]. This could be interpreted as sequels of less than optimal management during childhood and adolescence, though in the Finnish study, those diagnosed at an early age achieved greater adult height than those with late diagnosis [14].…”
Section: Results Of Present Treatment Regimens In 21ohd As Reflectedmentioning
confidence: 99%